'I Have to Act Like Everything's Okay': Menstruation, the Female Body, and the World of Work Organisations - Petra Poncarová; Radka Dudová (Gender a Výzkum)
Menstruation in the world of work organisations has so far from a sociological perspective remained an unexplored topic. Using exploratory research and the grounded theory method, this article seeks to capture how Czech women cope with menstruation in the workplace. Women interested in participating in the research were ﬁrst asked to answer a short online questionnaire. From this pool we chose nineteen women (ages 21-66) who differed from each other in terms of their professions, age, and the extent to which menstruation is limiting for them and conducted qualitative interviews with them. The interviews were transcribed verbatim and subsequently coded and analysed. This coding led to the creation of categories and themes representing menstruation management and its different strategies and the different usage of menstrual aids, menstruation in the space-time of work organisations, social norms associated with menstruation, planning associated with menstruation, and menstruation as a reminder of corporeality. The analysis showed that menstruating women face many obstacles while doing their paid work, which can discriminate them. Furthermore, it has been found that menstruation restricts women when performing their work. Menstruating women must adhere to social norms that dictate that they must conceal their menstruation and its attendant symptoms. The space-time of work organisations may not always correspond to the needs of menstruating women, whether they use disposable menstrual aids or more sustainable options. The research also addresses the fact that women's corporality within work organizations largely differs from men's corporality. Because the male body does not have speciﬁc needs like the menstruating body, it can be ignored, whereas women cannot ignore their bodies.